2012
DOI: 10.1007/s12264-012-1050-z
|View full text |Cite
|
Sign up to set email alerts
|

Progression of motor symptoms in Parkinson’s disease

Abstract: Parkinson's disease (PD) is a chronic progressive neurodegenerative disease that is clinically manifested by a triad of cardinal motor symptoms - rigidity, bradykinesia and tremor - due to loss of dopaminergic neurons. The motor symptoms of PD become progressively worse as the disease advances. PD is also a heterogeneous disease since rigidity and bradykinesia are the major complaints in some patients whereas tremor is predominant in others. In recent years, many studies have investigated the progression of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
78
0
6

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(89 citation statements)
references
References 87 publications
0
78
0
6
Order By: Relevance
“…Although most of the odds ratios for factors that predict a slower rate of progression were statistically significant, they were small and of questionable clinical relevance on the basis of this study. A slower rate of disease progression has been reported for females, younger patients, and patients with the tremor‐dominant form of PD . Interestingly, in contrast to the findings of ADAGIO, which showed that higher baseline severity (higher UPDRS scores) predicted a faster rate of progression in early disease, the results of the AFU analysis indicated that, at this moderate stage of the disease, higher baseline UPDRS scores predicted a somewhat slower rate of progression.…”
Section: Discussionmentioning
confidence: 57%
“…Although most of the odds ratios for factors that predict a slower rate of progression were statistically significant, they were small and of questionable clinical relevance on the basis of this study. A slower rate of disease progression has been reported for females, younger patients, and patients with the tremor‐dominant form of PD . Interestingly, in contrast to the findings of ADAGIO, which showed that higher baseline severity (higher UPDRS scores) predicted a faster rate of progression in early disease, the results of the AFU analysis indicated that, at this moderate stage of the disease, higher baseline UPDRS scores predicted a somewhat slower rate of progression.…”
Section: Discussionmentioning
confidence: 57%
“…PD has a high socioeconomic burden since it is slowly progressive and disease-modifying treatments are not available. PD presents with motor and non-motor symptoms [3, 4] that worsen with advancing age, leading to a need for assistance with all daily activities. Disease manifestation is characterized by the presence of Lewy bodies (abnormal protein aggregates containing α-synuclein), death of dopaminergic (DAergic) neurons in the substantia nigra (SN) projecting to the striatum, and microgliosis (accumulation of activated microglial cells) [5].…”
Section: Introductionmentioning
confidence: 99%
“…The cardinal clinical symptoms are bradykinesia, tremor, rigidity, and postural instability with the pathological characteristic of evolutional nigrostriatal dopaminergic neurodegeneration [2,3] . 1-Methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP) is a neurotoxin that induces parkinsonism in both humans [4] and non-human primates [5] with the cognitive, biochemical, histological and classical behavioral changes that occur in PD [6] .…”
Section: Introductionmentioning
confidence: 99%